Where Men Appear More Religious Than Women: Turning a Gender Lens on Religion in Israel - Schnabel, Landon (Journal for the scientific study of religion, 2018)
Past research, typically focused on Christians in Christian nations, has found that women tend to be more religious than men. This study uses original nationally representative data (N = 5,601) with strategic oversamples of minority groups to examine variation in how religion and gender intersect across ethnoreligious identities in Israel. We demonstrate that Israel diverges from the typical pattern of women appearing more religious than men. In fact, Israeli men are consistently more religious than Israeli women on commonly used measures and frequently more religious on a broader set of questions specific to Judaism and Israel. Subgroup analyses highlight the intersectional nature of gender and religion, showing that men's greater religiosity in Israel is limited to Jews, and, more specifically, nonsecular Jews. We suggest that gender gaps arise, at least in part, because religions are gendered institutions with gendered norms, expectations, and incentives, and that these norms, expectations, and incentives vary from religion to religion.